Financial Leverage Decisions And Earnings Per Share Optimization At Pt Telkom Indonesia (Persero) Tbk - Muhammad Helmy Reza; Fatana Suastrini (Academic Bright Collaboration, 2026)
Purpose – This study investigates the income effect resulting from financial leverage at PT Telkom Indonesia (Persero), Tbk. Specifically, it examines both the partial and simultaneous influence of financial leverage, measured by the Debt to Equity Ratio (DER) and Time Interest Earned Ratio (TIER), on Earnings Per Share (EPS) at PT Telkom Indonesia (Persero), Tbk. Furthermore, it identifies the variable that most dominantly affects EPS over the period 2013–2024. Methods – The research employs an associative approach with a case study methodology. Data were collected using a documentation technique. Analytical procedures included financial ratio analysis and multiple linear regression, conducted using SPSS version 27. Findings – Analysis using indifference analysis indicates that the financial leverage policy has not produced a positive income effect. Statistical analysis reveals that the F-test shows significant simultaneous effect of DER and TIER on EPS, with a significance level of 0.000 (<0.05). The t-test indicates that, partially, DER has a significant effect on EPS (significance level = 0.000 < 0.05) and TIER has a significant effect on EPS (significance level = 0.000 < 0.05). The Debt to Equity Ratio (DER) and Time Interest Earned Ratio (TIER) variables explained 64.8% of the fluctuations in Earnings Per Share (EPS). Research Implications – Practically, the findings of this study can serve as a reference for corporate decision-making in establishing financial policies. Additionally, potential investors may utilize the results as a basis for informed investment decisions. Originality – This study contributes to the financial management literature by examining the effect of Debt to Equity Ratio (DER) and Time Interest Earned Ratio (TIER) on the financial performance of PT Telkom Indonesia (Persero) Tbk during the 2013–2024 period. Unlike previous studies that generally analyze leverage variables across multiple sectors, this research provides an in-depth analysis within the telecommunications industry through a longitudinal case study approach. The findings offer empirical evidence regarding the dominant influence of financial leverage indicators on corporate performance and provide practical implications for corporate financial decision-making.